Representing Lives
XXXIV, 300 p.
Keywords: Representing Lives: Women and Auto/biography is an eclectic and comprehensive collection of essays, exploring contemporary issues and debates concerning women's auto-biographical representations from a range of disciplinary perspectives. With authoritative contributions from a number of prominent figures in the field of women's auto/biography, as well as innovative new voices, this volume offers a broad and contemporary lens on the issues and debates relevant to the act of representing women's lives. Drawing on a variety of theoretical frameworks and discussing theatre, literature, popular culture and women in history, these essays help to map out some of the new intellectual spaces inhabited by feminist scholarship in the 1990s.